Effect of Different Music on Visual Reaction Time. - Kundaikar, Ashmi Naik; Shetty, Aksha; Usgaonkar, Ugam P. S. (Optometry & Visual Performance, 2024)
Aim: The purpose of this study was to evaluate the effect of different music on visual reaction time. Methodology: Thirty subjects with visual acuity logMAR 0.00 and near vision N6 in both eyes and no binocular vision anomaly or ocular anomaly were included in this research. Subjects with any kind of ocular disease, arthritis, or muscle disorders were excluded. Psychological Experimental Building Language (PEBL) version 2.1 software was used to check the visual reaction time. Subjects listened to four different types of instrumental music (symphony, hard rock, Indian classical, and techno) randomly while performing the PEBL visual reaction time task in a dark room. The volume of the music was maintained at 80 dB, and the brightness of the screen was maintained at 100% throughout the experiment. Readings were taken before listening to music, during listening to music, and after listening to music. Statistical analysis was performed using SPSS software. Results: Thirty subjects (15 male and 15 female) aged between 18 and 25 years, with mean age of 20 ±1 years, participated in this study. Statistical analysis was performed using paired t-test. The Shapiro-Wilk test showed a significance departure from the normality, W (30)=0.908, p=0.013. There was no significant difference in reaction time before listening and after listening to classical music (p<0.178), whereas there was a significant difference before listening and after listening to techno (p<0.008), symphony (p<0.005), and hard rock (p<0.002). In all four music styles--techno (p<0.586), symphony (p<0.629), rock (p<0.349), and Indian classical (p<0.829)--there was no statistically significant difference in reaction time before listening and during listening to music. There was a significant difference during listening and after listening to all four music stylres: techno (p<0.030), classical (p<0.039), symphony (p<0.000), and hard rock (p<0.014). CONCLUSION: Listening to instrumental music such as techno, Indian classical, symphony, and rock has the effect of reducing visual reaction time during listening. Longer visual reaction time is shown after listening to music. The visual reaction time before and after listening to classical music is longer as compared to other music; possibly because it was the most disliked music out of the four music styles.